Action myoclonus-renal failure syndrome: Diagnostic applications of activity-based probes and lipid analysis - Gaspar, Paulo; Kallemeijn, Wouter W.; Strijland, Anneke; Scheij, Saskia; Van Eijk, Marco; Aten, Jan; Overkleeft, Herman S.; Balreira, Andrea; Zunke, Friederike; Schwake, Michael; Miranda, Clara Sa; Aerts, Johannes M. F. G. (Journal of Lipid Research, 2014)
Lysosomal integral membrane protein-2 (LIMP2) mediates traffi cking of glucocerebrosidase (GBA) to lysosomes. Defi ciency of LIMP2 causes action myoclonus-renal failure syndrome (AMRF). LIMP2-defi cient fi broblasts virtually lack GBA like the cells of patients with Gaucher disease (GD), a lysosomal storage disorder caused by mutations in the GBA gene. While GD is characterized by the presence of glucosylceramide-laden macrophages, AMRF patients do not show these. We studied the fate of GBA in relation to LIMP2 defi ciency by employing recently designed activity-based probes labeling active GBA molecules. We demonstrate that GBA is almost absent in lysosomes of AMRF fi broblasts. However, white blood cells contain considerable amounts of residual enzyme. Consequently, AMRF patients do not acquire lipid-laden macrophages and do not show increased plasma levels of macrophage markers, such as chitotriosidase, in contrast to GD patients. We next investigated the consequences of LIMP2 deficiency with respect to plasma glycosphingolipid levels. Plasma glucosylceramide concentration was normal in the AMRF patients investigated as well as in LIMP2-defi cient mice. However, a marked increase in the sphingoid base, glucosylsphingosine, was observed in AMRF patients and LIMP2-defi cient mice. Our results suggest that combined measurements of chitotriosidase and glucosylsphingosine can be used for convenient differential laboratory diagnosis of GD and AMRF. Copyright © 2014 by the American Society for Biochemistry and Molecular Biology, Inc.
CRIS-Team Scopus Importer:2020-10-21
Keywords: Gaucher disease; Glucocerebrosidase; Glucosylsphingosine; LIMP2/SCARB2; Macrophages/monocytes; Scavenger receptors; Sphingolipids; Storage diseases

Activation and Purification of ß-Glucocerebrosidase by Exploiting its Transporter LIMP-2 – Implications for Novel Treatment Strategies in Gaucher's and Parkinson's Disease - Dobert, Jan; Bub, Simon; Mächtel, Rebecca; Januliene, Dovile; Steger, Lisa; Regensburger, Martin; Wilfling, Sibylle; Chen, Jia Xuan; Dejung, Mario; Plötz, Sonja; Hehr, Ute; Moeller, Arne; et al. (Advanced Science, 2024)
Genetic variants of GBA1 can cause the lysosomal storage disorder Gaucher disease and are among the highest genetic risk factors for Parkinson's disease (PD). GBA1 encodes the lysosomal enzyme beta-glucocerebrosidase (GCase), which orchestrates the degradation of glucosylceramide (GluCer) in the lysosome. Recent studies have shown that GluCer accelerates α-synuclein aggregation, exposing GCase deficiency as a major risk factor in PD pathology and as a promising target for treatment. This study investigates the interaction of GCase and three disease-associated variants (p.E326K, p.N370S, p.L444P) with their transporter, the lysosomal integral membrane protein 2 (LIMP-2). Overexpression of LIMP-2 in HEK 293T cells boosts lysosomal abundance of wt, E326K, and N370S GCase and increases/rescues enzymatic activity of the wt and E326K variant. Using a novel purification approach, co-purification of untagged wt, E326K, and N370S GCase in complex with His-tagged LIMP-2 from cell supernatant of HEK 293F cells is achieved, confirming functional binding and trafficking for these variants. Furthermore, a single helix in the LIMP-2 ectodomain is exploited to design a lysosome-targeted peptide that enhances lysosomal GCase activity in PD patient-derived and control fibroblasts. These findings reveal LIMP-2 as an allosteric activator of GCase, suggesting a possible therapeutic potential of targeting this interaction.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Gaucher's disease (GD); GCase; LIMP-2; lysosomes; Parkinson's disease (PD); protein purification; β-glucocerebrosidase

Activation of β-glucocerebrosidase reduces pathological α-synuclein and restores lysosomal function in Parkinson’s patient midbrain neurons - Mazzulli, Joseph R.; Zunke, Friederike; Tsunemi, Taiji; Toker, Nicholas J.; Jeon, Sohee; Burbulla, Lena F.; Patnaik, Samarjit; Sidransky, Ellen; Marugan, Juan J.; Sue, Carolyn M.; Krainc, Dimitri (Journal of Neuroscience, 2016)
Parkinson’s disease (PD) is characterized by the accumulation of α-synuclein (α-syn) within Lewy body inclusions in the nervous system. There are currently no disease-modifying therapies capable of reducing α -syn inclusions in PD. Recent data has indicated that loss-offunction mutations in the GBA1 gene that encodes lysosomal β-glucocerebrosidase (GCase) represent an important risk factor for PD, and can lead to α -syn accumulation. Here we use a small-molecule modulator of GCase to determine whether GCase activation within lysosomes can reduce α-syn levels and ameliorate downstream toxicity. Using induced pluripotent stem cell (iPSC)-derived human midbrain dopamine (DA) neurons from synucleinopathy patients with different PD-linked mutations,wefind that a non-inhibitory small molecule modulator of GCase specifically enhanced activity within lysosomal compartments. This resulted in reduction of GCase substrates and clearance of pathological α-syn, regardless of the disease causing mutations. Importantly, the reduction of α-syn was sufficient to reverse downstream cellular pathologies induced by α-syn, including perturbations in hydrolase maturation and lysosomal dysfunction. These results indicate that enhancement of a single lysosomal hydrolase, GCase, can effectively reduce α-syn and provide therapeutic benefit in human midbrain neurons. This suggests that GCase activators may prove beneficial as treatments for PD and related synucleinopathies.
CRIS-Team Scopus Importer:2020-10-21
Keywords: Glucocerebrosidase; Induced pluripotent stem cells; Lysosomes; Parkinson’s disease; Synucleinopathy; α-synuclein

ADAM17 is required for EGF-R-induced intestinal tumors via IL-6 trans-signaling - Schmidt, Stefanie; Schumacher, Neele; Schwarz, Jeanette; Tangermann, Simone; Kenner, Lukas; Schlederer, Michaela; Sibilia, Maria; Linder, Markus; Altendorf-Hofmann, Annelore; Knoesel, Thomas; Gruber, Elisabeth S.; Oberhuber, Georg; et al. (Journal of Experimental Medicine, 2018)
Colorectal cancer is treated with antibodies blocking epidermal growth factor receptor (EGF-R), but therapeutic success is limited. EGF-R is stimulated by soluble ligands, which are derived from transmembrane precursors by ADAM17-mediated proteolytic cleavage. In mouse intestinal cancer models in the absence of ADAM17, tumorigenesis was almost completely inhibited, and the few remaining tumors were of low-grade dysplasia. RNA sequencing analysis demonstrated downregulation of STAT3 and Wnt pathway components. Because EGF-R on myeloid cells, but not on intestinal epithelial cells, is required for intestinal cancer and because IL-6 is induced via EGF-R stimulation, we analyzed the role of IL-6 signaling. Tumor formation was equally impaired in IL-6-/- mice and sgp130Fc transgenic mice, in which only trans-signaling via soluble IL-6R is abrogated. ADAM17 is needed for EGF-R-mediated induction of IL-6 synthesis, which via IL-6 trans-signaling induces β-catenin-dependent tumorigenesis. Our data reveal the possibility of a novel strategy for treatment of colorectal cancer that could circumvent intrinsic and acquired resistance to EGF-R blockade.
CRIS-Team Scopus Importer:2020-10-21

Alpha Synuclein Connects the Gut-Brain Axis in Parkinson’s Disease Patients – A View on Clinical Aspects, Cellular Pathology and Analytical Methodology - Schaeffer, Eva; Kluge, Annika; Boettner, Martina; Zunke, Friederike; Cossais, Francois; Berg, Daniela; Arnold, Philipp (Frontiers in Cell and Developmental Biology, 2020)
Parkinson’s disease (PD) is marked by different kinds of pathological features, one hallmark is the aggregation of α-synuclein (aSyn). The development of aSyn pathology in the substantia nigra is associated to the manifestation of motor deficits at the time of diagnosis. However, most of the patients suffer additionally from non-motor symptoms, which may occur already in the prodromal phase of the disease years before PD is diagnosed. Many of these symptoms manifest in the gastrointestinal system (GIT) and some data suggest a potential link to the occurrence of pathological aSyn forms within the GIT. These clinical and pathological findings lead to the idea of a gut-brain route of aSyn pathology in PD. The identification of pathological aSyn in the intestinal system, e.g., by GIT biopsies, is therefore of highest interest for early diagnosis and early intervention in the phase of formation and propagation of aSyn. However, reliable methods to discriminate between physiological and pathological forms of enteral aSyn on the cellular and biochemical level are still missing. Moreover, a better understanding of the physiological function of aSyn within the GIT as well as its structure and pathological aggregation pathways are crucial to understand its role within the enteric nervous system and its spreading from the gut to the brain. In this review, we summarize clinical manifestations of PD in the GIT, and discuss biochemical findings from enteral biopsies. The relevance of pathological aSyn forms, their connection to the gut-brain axis and new developments to identify pathologic forms of aSyn by structural features are critically reviewed.
CRIS-Team Scopus Importer:2020-10-21
Keywords: alpha synuclein; gastrointestinal tract; gut-brain axis; Parkinson’s disease; ultra-structural analysis

Calcium negatively regulates meprin b activity and attenuates substrate cleavage - Arnold, Philipp; Schmidt, Frederike; Prox, Johannes; Zunke, Friederike; Pietrzik, Claus; Lucius, Ralph; Becker-Pauly, Christoph (The FASEB Journal, 2015)
The meprin β metalloproteinase is an important enzyme in extracellular matrix turnover, inflammation, and neurodegeneration in humans and mice. Previous studies showed a diminished cleavage of certain meprin β substrates in the presence of calcium, although the mechanism was not clear. With the help of a specific fluorogenic peptide assay and the human amyloid precursor protein as substrate, we demonstrated that the influence of calcium is most likely a direct effect on human meprin β itself. Analyzing the crystal structures of pro- and mature meprin β helped to identify a cluster of negatively charged amino acids forming a potential calcium binding site. Mutation of 2 of these residues (D204A and D245A) led to severe differences in proteolytic activity and cellular localization of meprin b. D245A was almost completely inactive and largely stored into intracellular vesicles, indicating severe misfolding of the protein. Astonishingly, D204A was not transported to the cell surface, but exhibited strong β-secretase activity, resulting in massive accumulation of Aβ-peptides. This could be explained by constitutive maturation of this meprin β mutant already in the early secretory pathway. We hypothesize that lacking D204 abrogates the capability of binding calcium in the catalytic domain, an important step for proper folding of the propeptide and subsequent inhibition of the protease. This is supported by the inhibition constant of calcium for meprin b (inhibitory constant 50 = 11 mM), which resembles the physiologic concentrations found in the endoplasmic reticulum. For instance, it was shown for amyotrophic lateral sclerosis that a loss of calcium in the endoplasmic reticulum leads to the misfolding of calcium-dependent proteins, which might also be relevant for proper function of meprin b.
CRIS-Team Scopus Importer:2020-10-21
Keywords: Amyloid b; APP; Protease; Protein folding

Cancer-Type Organic Anion Transporting Polypeptide 1B3 Is Localized in Lysosomes and Mediates Resistance against Kinase Inhibitors - Haberkorn, Bastian; Oswald, Stefan; Kehl, Niklas; Geßner, Arne; Taudte, Verena; Dobert, Jan; Zunke, Friederike; Fromm, Martin; König, Jörg (Molecular Pharmacology, 2022)
Cancer-type organic anion transporting polypeptide 1B3 (CtOATP1B3), a splice variant of the hepatic uptake transporter OATP1B3 (liver-type), is expressed in several tumor entities, including colorectal carcinoma (CRC) and breast cancer. In CRC, high OATP1B3 expression has been associated with reduced progression-free and overall survival. Several kinase inhibitors used for antitumor treatment are substrates and/or inhibitors of OATP1B3 (e.g., encorafenib, vemurafenib). The functional importance of CtOATP1B3 has not been elucidated so far. Human embryonic kidney 293 cells stably overexpressing Ct-OATP1B3 protein were established and compared with control cells. Confocal laser scanning microscopy, immunoblot, and proteomics-based expression analysis demonstrated that Ct-OATP1B3 protein is intracellularly localized in lysosomes of stably transfected cells. Cytotoxicity experiments showed that cells recombinantly expressing the Ct-OATP1B3 protein were more resistant against the kinase inhibitor encorafenib compared with control cells [e.g., encorafenib (100 mM) survival rates: 89.5% versus 52.8%]. In line with these findings, colorectal cancer DLD1 cells endogenously expressing Ct-OATP1B3 protein had poorer survival rates when the OATP1B3 substrate bromosulfophthalein (BSP) was coincubated with encorafenib or vemurafenib compared with the incubation with the kinase inhibitor alone. This indicates a competitive inhibition of Ct-OATP1B3–mediated uptake into lysosomes by BSP. Accordingly, mass spectrometry-based drug analysis of lysosomes showed a reduced lysosomal accumulation of encorafenib in DLD1 cells additionally exposed to BSP. These results demonstrate that Ct-OATP1B3 protein is localized in the lysosomal membrane and can mediate transport of certain kinase inhibitors into lysosomes, revealing a new mechanism of resistance.
Created from Fastlane, Scopus look-up

Cathepsin D Variants Associated With Neurodegenerative Diseases Show Dysregulated Functionality and Modified α-Synuclein Degradation Properties - Bunk, Josina; Prieto Huarcaya, Susy; Drobny, Alice; Dobert, Jan Philipp; Walther, Lina; Rose-John, Stefan; Arnold, Philipp; Zunke, Friederike (Frontiers in Cell and Developmental Biology, 2021)
Cathepsin D (CTSD) is a lysosomal protease important for the degradation of various substrates, including disease-associated proteins like α-synuclein (a-syn), amyloid precursor protein (APP) and tau, all of which tend to aggregate if not efficiently degraded. Hence, it is not surprising that genetic variants within the CTSD gene have been linked to neurodegenerative diseases, like Parkinson’s and Alzheimer’s disease (PD, AD), as well as the lysosomal storage disorder neuronal ceroid lipofuscinosis type-10 (NCL10). Although recent studies have shown the molecular dependence of substrate degradation via CTSD within autophagic pathways, only little is known about the precise role of lysosomal CTSD function in disease development. We here performed biochemical, cellular and structural analyses of eleven disease-causing CTSD point mutations found in genomic sequencing data of patients to understand their role in neurodegeneration. These CTSD variants were analyzed for cellular localization, maturation and enzymatic activity in overexpression analyses. Moreover, for PD-associated mutants, intracellular degradation of a-syn was monitored. In summary, our results suggest that NCL10-associated CTSD variants are significantly impaired in lysosomal maturation and enzymatic activity, whereas the AD- and PD-associated variants seemed rather unaffected, indicating normal maturation, and lysosomal presence. Interestingly, a PD-associated CTSD variant (A239V) exhibited increased enzymatic activity accompanied by enhanced a-syn degradation. By structural analyses of this mutant utilizing molecular dynamics simulation (MDS), we identified a structural change within a loop adjacent to the catalytic center leading to a higher flexibility and potentially accelerated substrate exchange rates. Our data sheds light onto the role of CTSD in disease development and helps to understand the structural regulation of enzymatic function, which could be utilized for targeted CTSD activation. Because of the degradative function of CTSD, this enzyme is especially interesting for therapeutic strategies tackling protein aggregates in neurodegenerative disorders.
CRIS-Team Scopus Importer:2021-03-12
Keywords: alpha-synuclein; cathepsin D; lysosomal degradation; lysosomes; molecular dynamics simulation; neuronal ceroid lipofuscinoses; Parkinson’s disease

Cell Surface Processing of CD109 by Meprin β Leads to the Release of Soluble Fragments and Reduced Expression on Extracellular Vesicles - Lueckstaedt, Wiebke; Bub, Simon; Koudelka, Tomas; Pavlenko, Egor; Peters, Florian; Somasundaram, Prasath; Becker-Pauly, Christoph; Lucius, Ralph; Zunke, Friederike; Arnold, Philipp (Frontiers in Cell and Developmental Biology, 2021)
Cluster of differentiation 109 (CD109) is a glycosylphosphatidylinositol (GPI)-anchored protein expressed on primitive hematopoietic stem cells, activated platelets, CD4+ and CD8+ T cells, and keratinocytes. In recent years, CD109 was also associated with different tumor entities and identified as a possible future diagnostic marker linked to reduced patient survival. Also, different cell signaling pathways were proposed as targets for CD109 interference including the TGFβ, JAK-STAT3, YAP/TAZ, and EGFR/AKT/mTOR pathways. Here, we identify the metalloproteinase meprin β to cleave CD109 at the cell surface and thereby induce the release of cleavage fragments of different size. Major cleavage was identified within the bait region of CD109 residing in the middle of the protein. To identify the structural localization of the bait region, homology modeling and single-particle analysis were applied, resulting in a molecular model of membrane-associated CD109, which allows for the localization of the newly identified cleavage sites for meprin β and the previously published cleavage sites for the metalloproteinase bone morphogenetic protein-1 (BMP-1). Full-length CD109 localized on extracellular vesicles (EVs) was also identified as a release mechanism, and we can show that proteolytic cleavage of CD109 at the cell surface reduces the amount of CD109 sorted to EVs. In summary, we identified meprin β as the first membrane-bound protease to cleave CD109 within the bait region, provide a first structural model for CD109, and show that cell surface proteolysis correlates negatively with CD109 released on EVs.
CRIS-Team Scopus Importer:2021-04-02
Keywords: CD109; exosomes; extracellular vesicles; macroglobulin; meprin β; TEM; TEP1r

Characterization of the complex formed by β-glucocerebrosidase and the lysosomal integral membrane protein type-2 - Zunke, Friederike; Andresen, Lisa; Wesseler, Sophia; Groth, Johann; Arnold, Philipp; Rothaug, Michelle; Mazzulli, Joseph R.; Krainc, Dimitri; Blanz, Judith; Saftig, Paul; Schwake, Michael (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The lysosomal integral membrane protein type-2 (LIMP-2) plays a pivotal role in the delivery of β-glucocerebrosidase (GC) to lysosomes. Mutations in GC result in Gaucher's disease (GD) and are the major genetic risk factor for the development of Parkinson's disease (PD). Variants in the LIMP-2 gene cause action myoclonus-renal failure syndrome and also have been linked to PD. Given the importance of GC and LIMP-2 in disease pathogenesis, we studied their interaction sites in more detail. Our previous data demonstrated that the crystal structure of LIMP-2 displays a hydrophobic three-helix bundle composed of helices 4, 5, and 7, of which helix 5 and 7 are important for ligand binding. Here, we identified a similar helical motif in GC through surface potential analysis. Coimmunoprecipitation and immunofluorescence studies revealed a triple-helical interface region within GC as critical for LIMP-2 binding and lysosomal transport. Based on these findings, we generated a LIMP-2 helix 5-derived peptide that precipitated and activated recombinant wild-type and GD-associated N370S mutant GC in vitro. The helix 5 peptide fused to a cellpenetrating peptide also activated endogenous lysosomal GC and reduced α-synuclein levels, suggesting that LIMP-2-derived peptides can be used to activate endogenous as well as recombinant wild-type or mutant GC efficiently. Our data also provide a structural model of the LIMP-2/GC complex that will facilitate the development of GC chaperones and activators as potential therapeutics for GD, PD, and related synucleinopathies.
CRIS-Team Scopus Importer:2020-10-21
Keywords: Gaucher's disease; GC activators; LIMP-2; Parkinson's disease; β-glucocerebrosidase

Computational decomposition reveals reshaping of the SARS‐CoV‐2–ACE2 interface among viral variants expressing the N501Y mutation - Socher, Eileen; Conrad, Marcus; Heger, Lukas; Paulsen, Friedrich; Sticht, Heinrich; Zunke, Friederike; Arnold, Philipp (Journal of Cellular Biochemistry, 2021)
Variants of concern of the SARS-CoV-2 virus with an asparagine-to-tyrosine substitution at position 501 (N501Y) in the receptor-binding domain (RBD) show enhanced infectivity compared to wild-type, resulting in an altered pandemic situation in affected areas. These SARS-Cov-2 variants comprise the two Alpha variants (B.1.1.7, United Kingdom and B.1.1.7 with the additional E484K mutation), the Beta variant (B.1.351, South Africa), and the Gamma variant (P.1, Brazil). Understanding the binding modalities between these viral variants and the host cell receptor ACE2 allows to depict changes, but also common motifs of virus–host cell interaction. The trimeric spike protein expressed at the viral surface contains the RBD that forms the molecular interface with ACE2. All the above-mentioned variants carry between one and three amino acid exchanges within the interface-forming region of the RBD, thereby altering the binding interface with ACE2. Using molecular dynamics (MD) simulations and decomposition of intermolecular contacts between the RBD and ACE2, we identified phenylalanine 486, glutamine 498, threonine 500, and tyrosine 505 as important interface-forming residues across viral variants. However, especially the N501Y exchange increased contact formation for this residue and also induced some local conformational changes. Comparing here, the in silico generated B.1.1.7 RBD–ACE2 complex with the now available experimentally solved structure reveals very similar behavior during MD simulation. We demonstrate, how computational methods can help to identify differences in conformation as well as contact formation for newly emerging viral variants. Altogether, we provide extensive data on all N501Y expressing SARS-CoV-2 variants of concern with respect to their interaction with ACE2 and how this induces reshaping of the RBD–ACE2 interface.

Corrigendum: Cathepsin D Variants Associated With Neurodegenerative Diseases Show Dysregulated Functionality and Modified α-Synuclein Degradation Properties (Frontiers in Cell and Developmental Biology, (2021), 9, (581805), 10.3389/fcell.2021.581805) - Bunk, Josina; Prieto Huarcaya, Susy; Drobny, Alice; Dobert, Jan; Walther, Lina; Rose-John, Stefan; Arnold, Philipp; Zunke, Friederike (Frontiers in Cell and Developmental Biology, 2021)
In the original article, there was a mistake in Figure 1C as published. In the Coomassie brilliant blue (CBB) protein staining, which was used as additional loading control (besides GAPDH), 11 instead of 10 sample lanes (+ protein ladder) were shown in the original Figure 1C. This mistake resulted from an additional sample (transfection control), that was loaded on the far right. This lane was not shown in both immunoblots (CTSD and GAPDH), but accidentally was still shown in the CBB control. The corrected Figure 1C appears below. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated. (Figure presented.).
CRIS-Team Scopus Importer:2021-07-16
Keywords: alpha-synuclein; cathepsin D; lysosomal degradation; lysosomes; molecular dynamics simulation; neuronal ceroid lipofuscinoses; Parkinson's disease

Cryo-TEM structure of β-glucocerebrosidase in complex with its transporter LIMP-2 - Dobert, Jan; Schäfer, Jan-Hannes; Dal Maso, Thomas; Ravindran, Priyadarshini; Huard, Dustin J. E.; Socher, Eileen; Schildmeyer, Lisa A.; Lieberman, Raquel L.; Versées, Wim; Moeller, Arne; Zunke, Friederike; Arnold, Philipp (Nature Communications, 2025)
Targeting proteins to their final cellular destination requires transport mechanisms and nearly all lysosomal enzymes reach the lysosome via the mannose-6-phosphate receptor pathway. One of the few known exceptions is the enzyme β-glucocerebrosidase (GCase) that requires the lysosomal integral membrane protein type-2 (LIMP-2) as a proprietary lysosomal transporter. Genetic variations in the GCase encoding gene GBA1 cause Gaucher’s disease (GD) and present the highest genetic risk factor to develop Parkinson’s disease (PD). Activators targeting GCase emerge as a promising therapeutic approach to treat GD and PD, with pre-clinical and clinical trials ongoing. In this study, we resolve the complex of GCase and LIMP-2 using cryo-electron microscopy with the aid of an engineered LIMP-2 shuttle and two GCase-targeted pro-macrobodies. We identify helix 5 and helix 7 of LIMP-2 to interact with a binding pocket in GCase, forming a mostly hydrophobic interaction interface supported by one essential salt bridge. Understanding the interplay of GCase and LIMP-2 on a structural level is crucial to identify potential activation sites and conceptualizing novel therapeutic approaches targeting GCase. Here, we unveil the protein structure of a mannose-6-phosphate-independent lysosomal transport complex and provide fundamental knowledge for translational clinical research to overcome GD and P
Keywords: Cryoelectron microscopy; Enzymes; Membrane proteins; Parkinson's disease

Detection of neuron-derived pathological alpha-synuclein in blood - Kluge, Annika; Bunk, Josina; Schaeffer, Eva; Drobny, Alice; Xiang, Wei; Knacke, Henrike; Bub, Simon; Lueckstaedt, Wiebke; Arnold, Philipp; Lucius, Ralph; Berg, Daniela; Zunke, Friederike (Brain, 2022)
To date, no reliable clinically applicable biomarker has been established for Parkinson's disease. Our results indicate that a long anticipated blood test for Parkinson's disease may be realized. Following the isolation of neuron-derived extracellular vesicles of Parkinson's disease patients and non-Parkinson's disease individuals, immunoblot analyses were performed to detect extracellular vesicle-derived alpha-synuclein. Pathological alpha-synuclein forms derived from neuronal extracellular vesicles could be detected under native conditions and were significantly increased in all individuals with Parkinson's disease and clearly distinguished disease from the non-disease state. By performing an alpha-synuclein seeding assay these soluble conformers could be amplified and seeding of pathological protein folding was demonstrated. Amplified alpha-synuclein conformers exhibited beta-sheet-rich structures and a fibrillary appearance. Our study demonstrates that the detection of pathological alpha-synuclein conformers from neuron-derived extracellular vesicles from blood plasma samples has the potential to evolve into a blood-biomarker of Parkinson's disease that is still lacking so far. Moreover, the distribution of seeding-competent alpha-synuclein within blood exosomes sheds a new light of pathological disease mechanisms in neurodegenerative disorders.
CRIS-Team WoS Importer:2022-07-01
Keywords: α-synuclein; Parkinson’s disease; biomarker; neuron-derived extracellular vesicles; seeding assay

Editorial: Intracellular Mechanisms of α-Synuclein Processing. - Zunke, Friederike; Winner, Beate; Richter, Franziska; Caraveo, Gabriela (Frontiers in Cell and Developmental Biology, 2021)
CRIS-Team Scopus Importer:2021-10-08
Keywords: alpha-synuclein; lysosomes; neurodegeneration; protein misfolding; spread; synucleinopathies

From Lysosomal Storage Disorders to Parkinson's Disease – Challenges and Opportunities - Mächtel, Rebecca; Boros, Fanni Annamaria; Dobert, Jan; Arnold, Philipp; Zunke, Friederike (Journal of Molecular Biology, 2023)
Lysosomes are specialized organelles with an acidic pH that act as recycling hubs for intracellular and extracellular components. They harbour numerous different hydrolytic enzymes to degrade substrates like proteins, peptides, and glycolipids. Reduced catalytic activity of lysosomal enzymes can cause the accumulation of these substrates and loss of lysosomal integrity, resulting in lysosomal dysfunction and lysosomal storage disorders (LSDs). Post-mitotic cells, such as neurons, seem to be highly sensitive to damages induced by lysosomal dysfunction, thus LSDs often manifest with neurological symptoms. Interestingly, some LSDs and Parkinson's disease (PD) share common cellular pathomechanisms, suggesting convergence of aetiology of the two disease types. This is further underlined by genetic associations of several lysosomal genes involved in LSDs with PD. The increasing number of lysosome-associated genetic risk factors for PD makes it necessary to understand functions and interactions of lysosomal proteins/enzymes both in health and disease, thereby holding the potential to identify new therapeutic targets. In this review, we highlight genetic and mechanistic interactions between the complex lysosomal network, LSDs and PD, and elaborate on methodical challenges in lysosomal research.
CRIS-Team Scopus Importer:2023-03-24
Keywords: lysosomal enzymes; lysosomal storage disorder; lysosome; neurodegeneration; Parkinson's disease

Functional characterization of colon cancer-associated mutations in ADAM17: Modifications in the pro-domain interfere with trafficking and maturation - Pavlenko, Egor; Cabron, Anne-Sophie; Arnold, Philipp; Dobert, Jan Philipp; Rose-John, Stefan; Zunke, Friederike (International Journal of Molecular Sciences, 2019)
Colorectal cancer is one of the most commonly diagnosed malignancies in the Western world and is associated with elevated expression and activity of epidermal growth factor receptors (EGF-R). The metalloproteinase ADAM17 is involved in EGF-R activation by processing EGF-R ligands from membrane-bound pro-ligands. Underlining the link between colon cancer and ADAM17, genetic intestinal cancer models in ADAM17-deficient mice show a reduced tumor burden. In this study, we characterize point mutations within the ADAM17 gene found in the tissue of colon cancer patients. In order to shed light on the role of ADAM17 in cancer development, as well as into the mechanisms that regulate maturation and cellular trafficking of ADAM17, we here perform overexpression studies of four ADAM17 variants located in the pro-, membrane-proximal- and cytoplasmic-domain of the ADAM17 protein in ADAM10/17-deficient HEK cells. Interestingly, we found a cancer-associated point mutation within the pro-domain of ADAM17 (R177C) to be most impaired in its proteolytic activity and trafficking to the cell membrane. By comparing this variant to an ADAM17 construct lacking the entire pro-domain, we discovered similar functional limitations and propose a crucial role of the pro-domain for ADAM17 maturation, cellular trafficking and thus proteolytic activity.
CRIS-Team Scopus Importer:2020-10-21
Keywords: ADAM17; Colon cancer; EGF-receptor; Metalloprotease; Secretory pathway; Shedding; Trafficking of membrane proteins; Tumor necrosis factor

Functional characterization of colon-cancer-associated variants in adam17 affecting the catalytic domain - Dobert, Jan Philipp; Cabron, Anne Sophie; Arnold, Philipp; Pavlenko, Egor; Rose-John, Stefan; Zunke, Friederike (Biomedicines, 2020)
Although extensively investigated, cancer is still one of the most devastating and lethal diseases in the modern world. Among different types, colorectal cancer (CRC) is most prevalent and mortal, making it an important subject of research. The metalloprotease ADAM17 has been implicated in the development of CRC due to its involvement in signaling pathways related to inflammation and cell proliferation. ADAM17 is capable of releasing membrane-bound proteins from the cell surface in a process called shedding. A deficiency of ADAM17 activity has been previously shown to have protective effects against CRC in mice, while an upregulation of ADAM17 activity is suspected to facilitate tumor development. In this study, we characterize ADAM17 variants found in tissue samples of cancer patients in overexpression studies. We here focus on point mutations identified within the catalytic domain of ADAM17 and could show a functional dysregulation of the CRC-associated variants. Since the catalytic domain of ADAM17 is the only region structurally determined by crystallography, we study the effect of each point mutation not only to learn more about the role of ADAM17 in cancer, but also to investigate the structure–function relationships of the metalloprotease.
CRIS-Team Scopus Importer:2020-11-13
Keywords: ADAM17; AREG; Colorectal cancer (CRC); IL-6R; Shedding; TNFα

Gut-to-brain spreading of pathology in synucleinopathies: A focus on molecular signalling mediators - Schmitt, Verena; Masanetz, Rebecca Katharina; Weidenfeller, Martin; Ebbinghaus, Lara Savannah; Süß, Patrick; Rosshart, Stephan Patrick; von Hörsten, Stephan; Zunke, Friederike; Winkler, Jürgen; Xiang, Wei (Behavioural Brain Research, 2023)
Synucleinopathies are a group of neurodegenerative disorders, classically characterized by the accumulation of aggregated alpha synuclein (aSyn) in the central nervous system. Parkinson's disease (PD) and multiple system atrophy (MSA) are the two prominent members of this family. Current treatment options mainly focus on the motor symptoms of these diseases. However, non-motor symptoms, including gastrointestinal (GI) symptoms, have recently gained particular attention, as they are frequently associated with synucleinopathies and often arise before motor symptoms. The gut-origin hypothesis has been proposed based on evidence of an ascending spreading pattern of aggregated aSyn from the gut to the brain, as well as the comorbidity of inflammatory bowel disease and synucleinopathies. Recent advances have shed light on the mechanisms underlying the progression of synucleinopathies along the gut-brain axis. Given the rapidly expanding pace of research in the field, this review presents a summary of the latest findings on the gut-to-brain spreading of pathology and potential pathology-reinforcing mediators in synucleinopathies. Here, we focus on 1) gut-to-brain communication pathways, including neuronal pathways and blood circulation, and 2) potential molecular signalling mediators, including bacterial amyloid proteins, microbiota dysbiosis-induced alterations in gut metabolites, as well as host-derived effectors, including gut-derived peptides and hormones. We highlight the clinical relevance and implications of these molecular mediators and their possible mechanisms in synucleinopathies. Moreover, we discuss their potential as diagnostic markers in distinguishing the subtypes of synucleinopathies and other neurodegenerative diseases, as well as for developing novel individualized therapeutic options for synucleinopathies.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Alpha synuclein; Gut-to-brain communication; Inflammatory bowel disease; Multiple system atrophy; Parkinson's disease

Interaction of Alpha Synuclein and Microtubule Organization Is Linked to Impaired Neuritic Integrity in Parkinson’s Patient-Derived Neuronal Cells - Schneider, Yanni; Drobny, Alice; Prots, Iryna; Zunke, Friederike; Xiang, Wei; Seebauer, Lukas; Schneider, Yanni; Drobny, Alice; Ploetz, Sonja; Koudelka, Tomas; Tholey, Andreas; Prots, Iryna; et al. (International Journal of Molecular Sciences, 2022)
Parkinson’s disease (PD) is neuropathologically characterized by the loss of dopaminergic neurons and the deposition of aggregated alpha synuclein (aSyn). Mounting evidence suggests that neuritic degeneration precedes neuronal loss in PD. A possible underlying mechanism could be the interference of aSyn with microtubule organization in the neuritic development, as implied by sev-eral studies using cell-free model systems. In this study, we investigate the impact of aSyn on mi-crotubule organization in aSyn overexpressing H4 neuroglioma cells and midbrain dopaminergic neuronal cells (mDANs) generated from PD patient-derived human induced pluripotent stem cells (hiPSCs) carrying an aSyn gene duplication (SNCADupl). An unbiased mass spectrometric analysis reveals a preferential binding of aggregated aSyn conformers to a number of microtubule elements. We confirm the interaction of aSyn with beta tubulin III in H4 and hiPSC-derived mDAN cell model systems, and demonstrate a remarkable redistribution of tubulin isoforms from the soluble to insoluble fraction, accompanied by a significantly increased insoluble aSyn level. Concordantly, SNCA-Dupl mDANs show impaired neuritic phenotypes characterized by perturbations in neurite initiation and outgrowth. In summary, our findings suggest a mechanistic pathway, through which aSyn aggregation interferes with microtubule organization and induces neurite impairments.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Alpha-synuclein; IPSC; Microtubule; Neurite; Neurodegeneration; Parkinson’s disease; SNCA duplication

LAMP-2 deficiency leads to hippocampal dysfunction but normal clearance of neuronal substrates of chaperone-mediated autophagy in a mouse model for Danon disease - Rothaug, Michelle; Stroobants, Stijn; Schweizer, Michaela; Peters, Judith; Zunke, Friederike; Allerding, Mirka; D'Hooge, Rudi; Saftig, Paul; Blanz, Judith (Acta Neuropathologica Communications, 2015)
The Lysosomal Associated Membrane Protein type-2 (LAMP-2) is an abundant lysosomal membrane protein with an important role in immunity, macroautophagy (MA) and chaperone-mediated autophagy (CMA). Mutations within the Lamp2 gene cause Danon disease, an X-linked lysosomal storage disorder characterized by (cardio)myopathy and intellectual dysfunction. The pathological hallmark of this disease is an accumulation of glycogen and autophagic vacuoles in cardiac and skeletal muscle that, along with the myopathy, is also present in LAMP-2-deficient mice. Intellectual dysfunction observed in the human disease suggests a pivotal role of LAMP-2 within brain. LAMP-2A, one specific LAMP-2 isoform, was proposed to be important for the lysosomal degradation of selective proteins involved in neurodegenerative diseases such as Huntington's and Parkinson's disease. To elucidate the neuronal function of LAMP-2 we analyzed knockout mice for neuropathological changes, MA and steady-state levels of CMA substrates. The absence of LAMP-2 in murine brain led to inflammation and abnormal behavior, including motor deficits and impaired learning. The latter abnormality points to hippocampal dysfunction caused by altered lysosomal activity, distinct accumulation of p62-positive aggregates, autophagic vacuoles and lipid storage within hippocampal neurons and their presynaptic terminals. The absence of LAMP-2 did not apparently affect MA or steady-state levels of selected CMA substrates in brain or neuroblastoma cells under physiological and prolonged starvation conditions. Our data contribute to the understanding of intellectual dysfunction observed in Danon disease patients and highlight the role of LAMP-2 within the central nervous system, particularly the hippocampus.
CRIS-Team Scopus Importer:2020-10-21

Late-onset Krabbe disease presenting as spastic paraplegia – implications of GCase and CTSB/D - Mächtel, Rebecca; Dobert, Jan; Hehr, Ute; Weiß, Alexander; Kettwig, Matthias; Laugwitz, Lucia; Groeschel, Samuel; Schmidt, Manuel; Arnold, Philipp; Regensburger, Martin; Zunke, Friederike (Annals of Clinical and Translational Neurology, 2024)
Objective: Krabbe disease (KD) is a multisystem neurodegenerative disorder with severe disability and premature death, mostly with an infancy/childhood onset. In rare cases of late-onset phenotypes, symptoms are often milder and difficult to diagnose. We here present a translational approach combining diagnostic and biochemical analyses of a male patient with a progressive gait disorder starting at the age of 44 years, with a final diagnosis of late-onset KD (LOKD). Methods: Additionally to cerebral MRI, protein structural analyses of the β-galactocerebrosidase protein (GALC) were performed. Moreover, expression, lysosomal localization, and activities of β-glucocerebrosidase (GCase), cathepsin B (CTSB), and cathepsin D (CTSD) were analyzed in leukocytes, fibroblasts, and lysosomes of fibroblasts. Results: Exome sequencing revealed biallelic likely pathogenic variants: GALC exons 11–17: 33 kb deletion; exon 4: missense variant (c.334A>G, p.Thr112Ala). We detected a reduced GALC activity in leukocytes and fibroblasts. While histological KD phenotypes were absent in fibroblasts, they showed a significantly decreased activities of GCase, CTSB, and CTSD in lysosomal fractions, while expression levels were unaffected. Interpretation: The presented LOKD case underlines the age-dependent appearance of a mildly pathogenic GALC variant and its interplay with other lysosomal proteins. As GALC malfunction results in reduced ceramide levels, we assume this to be causative for the here described decrease in CTSB and CTSD activity, potentially leading to diminished GCase activity. Hence, we emphasize the importance of a functional interplay between the lysosomal enzymes GALC, CTSB, CTSD, and GCase, as well as between their substrates, and propose their conjoined contribution in KD pathology.
CRIS-Team Scopus Importer:2024-06-14
Keywords: cathepsin B; cathepsin D; enzymatic activity; Krabbe disease; late-onset; β-glucocerebrosidase

LIMP-2 expression is critical for β-glucocerebrosidase activity and α-synuclein clearance - Rothaug, Michelle; Zunke, Friederike; Mazzulli, Joseph R.; Schweizer, Michaela; Altmeppen, Hermann; Luellmann-Rauch, Renate; Kallemeijn, Wouter W.; Gaspar, Paulo; Aerts, Johannes M.; Glatzel, Markus; Saftig, Paul; Krainc, Dimitri; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Mutations within the lysosomal enzyme β-glucocerebrosidase (GC) result in Gaucher disease and represent a major risk factor for developing Parkinson disease (PD). Loss of GC activity leads to accumulation of its substrate glucosylceramide and α-synuclein. Since lysosomal activity of GC is tightly linked to expression of its trafficking receptor, the lysosomal integral membrane protein type-2 (LIMP-2), we studied α-synuclein metabolism in LIMP-2-deficient mice. These mice showed an α-synuclein dosage-dependent phenotype, including severe neurological impairments and premature death. In LIMP-2-deficient brains a significant reduction in GC activity led to lipid storage, disturbed autophagic/lysosomal function, and α-synuclein accumulation mediating neurotoxicity of dopaminergic (DA) neurons, apoptotic cell death, and inflammation. Heterologous expression of LIMP-2 accelerated clearance of overexpressed α-synuclein, possibly through increasing lysosomal GC activity. In surviving DA neurons of human PD midbrain, LIMP-2 levels were increased, probably to compensate for lysosomal GC deficiency. Therefore, we suggest that manipulating LIMP-2 expression to increase lysosomal GC activity is a promising strategy for the treatment of synucleinopathies.
CRIS-Team Scopus Importer:2020-10-21
Keywords: AMRF; C57/BL6-J; GD; PME; SCARB2

Lysosomal integral membrane protein type-2 (LIMP-2/SCARB2) is a substrate of cathepsin-F, a cysteine protease mutated in type-B-Kufs-disease - Peters, Judith; Rittger, Andrea; Weisner, Rebecca; Knabbe, Johannes; Zunke, Friederike; Rothaug, Michelle; Damme, Markus; Berkovic, Samuel F.; Blanz, Judith; Saftig, Paul; Schwake, Michael (Biochemical and Biophysical Research Communications, 2015)
The lysosomal integral membrane protein type-2 (LIMP-2/SCARB2) has been identified as a receptor for enterovirus 71 uptake and mannose-6-phosphate-independent lysosomal trafficking of the acid hydrolase β-glucocerebrosidase. Here we show that LIMP-2 undergoes proteolytic cleavage mediated by lysosomal cysteine proteases. Heterologous expression and in vitro studies suggest that cathepsin-F is mainly responsible for the lysosomal processing of wild-type LIMP-2. Furthermore, examination of purified lysosomes revealed that LIMP-2 undergoes proteolysis in vivo. Mutations in the gene encoding cathepsin-F (CTSF) have recently been associated with type-B-Kufs-disease, an adult form of neuronal ceroid-lipofuscinosis. In this study we show that disease-causing cathepsin-F mutants fail to cleave LIMP-2. Our findings provide evidence that LIMP-2 represents an in vivo substrate of cathepsin-F with relevance for understanding the pathophysiology of type-B-Kufs-disease.
CRIS-Team Scopus Importer:2020-10-21
Keywords: Cathepsin-F; Kufs disease; LIMP-2; Lysosomal storage disease; Neuronal ceroid-lipofuscinosis

Mannose 6-phosphate-independent Lysosomal Sorting of LIMP-2 - Blanz, Judith; Zunke, Friederike; Markmann, Sandra; Damme, Markus; Braulke, Thomas; Saftig, Paul; Schwake, Michael (Traffic, 2015)
The widely accepted view that β-glucocerebrosidase (GC) is targeted to lysosomes by the lysosomal integral membrane protein type 2 (LIMP-2) independent of the mannose 6-phosphate (M6P) pathway has been recently challenged by the identification of a putative M6P residue in the crystalized LIMP-2 ectodomain. We demonstrate that LIMP-2 and GC reach lysosomes independent of the M6P pathway in fibroblasts and in purified liver lysosomes. Additionally, LIMP-2 could not be affinity-purified using M6P-specific antibodies. Our data prove M6P-independent lysosomal sorting of LIMP-2 and GC. The lysosomal integral membrane protein type 2 (LIMP-2/SCARB2) has been described as a mannose 6-phosphate (M6P)-independent trafficking receptor for β-glucocerebrosidase (GC). Recently, a putative M6P residue in a crystal structure of a recombinantly expressed LIMP-2 ectodomain has been reported. Based on surface plasmon resonance and fluorescence lifetime imaging analyses, it was suggested that the interaction of soluble LIMP-2 with the cation-independent M6P receptor (MPR) results in M6P-dependent targeting of LIMP-2 to lysosomes. As the physiological relevance of this observation was not addressed, we investigated M6P-dependent delivery of LIMP-2 to lysosomes in murine liver and mouse embryonic fibroblasts. We demonstrate that LIMP-2 and GC reach lysosomes independent of the M6P pathway. In fibroblasts lacking either MPRs or the M6P-forming N-acetylglucosamine (GlcNAc)-1-phosphotransferase, LIMP-2 still localizes to lysosomes. Immunoblot analyses also revealed comparable LIMP-2 levels within lysosomes purified from liver of wild-type (wt) and GlcNAc-1-phosphotransferase-defective mice. Heterologous expression of the luminal domain of LIMP-2 in wild-type, LIMP-2-deficient and GlcNAc-1-phosphotransferase-defective cells further established that the M6P modification is dispensable for lysosomal sorting of LIMP-2. Finally, cathepsin Z, a known GlcNAc-1-phosphotransferase substrate, but not LIMP-2, could be precipitated with M6P-specific antibodies. These data prove M6P-independent lysosomal sorting of LIMP-2 and subsequently GC in vivo.
CRIS-Team Scopus Importer:2020-10-21
Keywords: Gaucher disease; LIMP-2/SCARB2; Mannose 6-phosphate; Mannose 6-phosphate receptor; β-glucocerebrosidase

Modeling neuronopathic storage diseases with patient-derived culture systems - Zunke, Friederike; Mazzulli, Joseph R. (Neurobiology of Disease, 2019)
Lysosomes are organelles involved in the degradation and recycling of macromolecules, and play a critical role in sensing metabolic information in the cell. A class of rare metabolic diseases called lysosomal storage disorders (LSD) are characterized by lysosomal dysfunction and the accumulation of macromolecular substrates. The central nervous system appears to be particularly vulnerable to lysosomal dysfunction, since many LSDs are characterized by severe, widespread neurodegeneration with pediatric onset. Furthermore, variants in lysosomal genes are strongly associated with some common neurodegenerative disorders such as Parkinson's disease (PD). To better understand disease pathology and develop novel treatment strategies, it is critical to study the fundamental molecular disease mechanisms in the affected cell types that harbor endogenously expressed mutations. The discovery of methods for reprogramming of patient-derived somatic cells into induced pluripotent stem cells (iPSCs), and their differentiation into distinct neuronal and glial cell types, have provided novel opportunities to study mechanisms of lysosomal dysfunction within the relevant, vulnerable cell types. These models also expand our ability to develop and test novel therapeutic targets. We discuss recently developed methods for iPSC differentiation into distinct neuronal and glial cell types, while addressing the need for meticulous experimental techniques and parameters that are essential to accurately identify inherent cellular pathologies. iPSC models for neuronopathic LSDs and their relationship to sporadic age-related neurodegeneration are also discussed. These models should facilitate the discovery and development of personalized therapies in the future.
CRIS-Team Scopus Importer:2020-10-21

Molecular dynamics simulations of the delta and omicron SARS-CoV-2 spike – ACE2 complexes reveal distinct changes between both variants - Socher, Eileen; Heger, Lukas; Paulsen, Friedrich; Zunke, Friederike; Arnold, Philipp (Computational and Structural Biotechnology Journal, 2022)
SARS-CoV-2, the virus causing the COVID-19 pandemic, changes frequently through the appearance of mutations constantly leading to new variants. However, only few variants evolve as dominating and will be considered as “Variants of Concern” (VOCs) by the world health organization (WHO). At the end of 2020 the alpha (B.1.1.7) variant appeared in the United Kingdom and dominated the pandemic situation until mid of 2021 when it was substituted by the delta variant (B.1.617.2) that first appeared in India as predominant. At the end of 2021, SARS-CoV-2 omicron (B.1.1.529) evolved as the dominating variant. Here, we use in silico modeling and molecular dynamics (MD) simulations of the receptor-binding domain of the viral spike protein and the host cell surface receptor ACE2 to analyze and compare the interaction pattern between the wild type, delta and omicron variants. We identified residue 493 in delta (glutamine) and omicron (arginine) with altered binding properties towards ACE2.<br
Keywords: COVID-19; SARS-CoV-2; B.1.427/B.1.429; B.1.617.2; B.1.617.1; B.1.1.529; Epsilon variant; Delta variant; Kappa variant; Omicron variant; VOC; Spike protein; Receptor-binding domain; ACE2; Receptor interface; Molecular dynamics simulations

Mutations in the B.1.1.7 SARS-CoV-2 Spike Protein Reduce Receptor-Binding Affinity and Induce a Flexible Link to the Fusion Peptide - Socher, Eileen; Conrad, Marcus; Heger, Lukas; Paulsen, Friedrich; Sticht, Heinrich; Zunke, Friederike; Arnold, Philipp (Biomedicines, 2021)
The B.1.1.7 variant of the SARS-CoV-2 virus shows enhanced infectiousness over the wild type virus, leading to increasing patient numbers in affected areas. Amino acid exchanges within the SARS-CoV-2 spike protein variant of B.1.1.7 affect inter-monomeric contact sites within the trimer (A570D and D614G) as well as the ACE2-receptor interface region (N501Y), which comprises the receptor-binding domain (RBD) of the spike protein. However, the molecular consequences of mutations within B.1.1.7 on spike protein dynamics and stability or ACE2 binding are largely unknown. Here, molecular dynamics simulations comparing SARS-CoV-2 wild type with the B.1.1.7 variant revealed inter-trimeric contact rearrangements, altering the structural flexibility within the spike protein trimer. Furthermore, we found increased flexibility in direct spatial proximity of the fusion peptide due to salt bridge rearrangements induced by the D614G mutation in B.1.1.7. This study also implies a reduced binding affinity for B.1.1.7 with ACE2, as the N501Y mutation restructures the RBD-ACE2 interface, significantly decreasing the linear interaction energy between the RBD and ACE2. Our results demonstrate how mutations found within B.1.1.7 enlarge the flexibility around the fusion peptide and change the RBD-ACE2 interface. We anticipate our findings to be starting points for in depth biochemical and cell biological analyses of B.1.1.7.
CRIS-Team WoS Importer:2021-06-04
Keywords: COVID-19; SARS-CoV-2; B.1.1.7; molecular dynamics simulation; ACE2; receptor binding

Pathological alpha-syn aggregation is mediated by glycosphingolipid chain length and the physiological state of alpha-syn in vivo - Fredriksen, Kristina; Aivazidis, Stefanos; Sharma, Karan; Burbidge, Kevin J.; Pitcairn, Caleb; Zunke, Friederike; Gelyana, Eilrayna; Mazzulli, Joseph R. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
GBA1 mutations that encode lysosomal beta-glucocerebrosidase (GCase) cause the lysosomal storage disorder Gaucher disease (GD) and are strong risk factors for synucleinopathies, including Parkinson's disease and Lewy body dementia. Only a subset of subjects with GBA1 mutations exhibit neurodegeneration, and the factors that influence neurological phenotypes are unknown. We find that alpha-synuclein (alpha-syn) neuropathology induced by GCase depletion depends on neuronal maturity, the physiological state of alpha-syn, and specific accumulation of long-chain glycosphingolipid (GSL) GCase substrates. Reduced GCase activity does not initiate alpha-syn aggregation in neonatal mice or immature human midbrain cultures; however, adult mice or mature midbrain cultures that express physiological alpha-syn oligomers are aggregation prone. Accumulation of long-chain GSLs (>= C22), but not short-chain species, induced alpha-syn pathology and neurological dysfunction. Selective reduction of long-chain GSLs ameliorated alpha-syn pathology through lysosomal cathepsins. We identify specific requirements that dictate synuclein pathology in GD models, providing possible explanations for the phenotypic variability in subjects with GCase deficiency.
CRIS-Team WoS Importer:2021-12-31

Pharmacological dissection of K v7.1 channels in systemic and pulmonary arteries - Chadha, Preet S.; Zunke, Friederike; Davis, Alison J.; Jepps, Thomas A.; Linders, Joannes T. M.; Schwake, Michael; Towart, Rob; Greenwood, Iain A. (British Journal of Pharmacology, 2012)
BACKGROUND AND PURPOSE The aim of this study was to characterize the functional impact of KCNQ1-encoded voltage-dependent potassium channels (K v7.1) in the vasculature. EXPERIMENTAL APPROACH Mesenteric arteries, intrapulmonary arteries and thoracic aortae were isolated from adult rats. K v7.1 channel expression was established by fluorescence immunocytochemistry. Wire myography determined functionality of these channels in response to selective blockers and activators. Xenopus oocytes expressing K v7.1 channels were used to assess the effectiveness of selective K v7.1 channel blockers. KEY RESULTS K v7.1 channels were identified in arterial myocytes by immunocytochemistry. K v7.1 blockers HMR1556, L-768,673 (10 μM) and JNJ39490282 (JNJ282; 1 μM) had no contractile effects in arteries, whereas the pan-K v7 channel blocker linopirdine (10 μM) evoked robust contractions. Application of two compounds purported to activate K v7.1 channels, L-364 373 (R-L3) and mefenamic acid, relaxed mesenteric arteries preconstricted by methoxamine. These responses were reversed by HMR1556 or L-768,673 but not JNJ282. Similar effects were observed in the thoracic aorta and intrapulmonary arteries. CONCLUSIONS AND IMPLICATIONS In contrast to previous assumptions, K v7.1 channels expressed in arterial myocytes are functional ion channels. Although these channels do not appear to contribute to resting vascular tone, K v7.1 activators were effective vasorelaxants. © 2012 The Authors. British Journal of Pharmacology © 2012 The British Pharmacological Society.
CRIS-Team Scopus Importer:2020-10-21
Keywords: arterial tone; K; KCNQ; vascular smooth muscle; voltage-dependent K

Proteolysis of CD44 at the cell surface controls a downstream protease network - Woehner, Birte; Li, Wenjia; Hey, Sven; Drobny, Alice; Werny, Ludwig; Becker-Pauly, Christoph; Lucius, Ralph; Zunke, Friederike; Linder, Stefan; Arnold, Philipp (Frontiers in Molecular Biosciences, 2023)
The cell surface receptor cluster of differentiation 44 (CD44) is the main hyaluronan receptor of the human body. At the cell surface, it can be proteolytically processed by different proteases and was shown to interact with different matrix metalloproteinases. Upon proteolytic processing of CD44 and generation of a C-terminal fragment (CTF), an intracellular domain (ICD) is released after intramembranous cleavage by the γ-secretase complex. This intracellular domain then translocates to the nucleus and induces transcriptional activation of target genes. In the past CD44 was identified as a risk gene for different tumor entities and a switch in CD44 isoform expression towards isoform CD44s associates with epithelial to mesenchymal transition (EMT) and cancer cell invasion. Here, we introduce meprin β as a new sheddase of CD44 and use a CRISPR/Cas9 approach to deplete CD44 and its sheddases ADAM10 and MMP14 in HeLa cells. We here identify a regulatory loop at the transcriptional level between ADAM10, CD44, MMP14 and MMP2. We show that this interplay is not only present in our cell model, but also across different human tissues as deduced from GTEx (Gene Tissue Expression) data. Furthermore, we identify a close relation between CD44 and MMP14 that is also reflected in functional assays for cell proliferation, spheroid formation, migration and adhesion.
CRIS-Team Scopus Importer:2023-03-24
Keywords: ADAM10; CD44; cell adhesion; meprin β; MMP14; MMP2; shedding; tumor spheroid

Recombinant pro-CTSD (cathepsin D) enhances SNCA/α-Synuclein degradation in α-Synucleinopathy models. - Huarcaya, Alice Prieto; Drobny, Susy; Marques, Andre R. A.; Di Spiezio, Alessandro; Dobert, Jan; Balta, Denise; Werner, Christian; Rizo Garza, Tania; Gallwitz, Lisa; Bub, Simon; Stojkovska, Iva; Belur, Nandkishore R.; et al. (Autophagy, 2022)
Parkinson disease (PD) is a neurodegenerative disorder characterized by the abnormal intracellular accumulation of SNCA/α-synuclein. While the exact mechanisms underlying SNCA pathology are not fully understood, increasing evidence suggests the involvement of autophagy as well as lysosomal deficiencies. Because CTSD (cathepsin D) has been proposed to be the major lysosomal protease involved in SNCA degradation, its deficiency has been linked to the presence of insoluble SNCA conformers in the brain of mice and humans as well as to the transcellular transmission of SNCA aggregates. We here postulate that SNCA degradation can be enhanced by the application of the recombinant human proform of CTSD (rHsCTSD). Our results reveal that rHsCTSD is efficiently endocytosed by neuronal cells, correctly targeted to lysosomes and matured to an enzymatically active protease. In dopaminergic neurons derived from induced pluripotent stem cells (iPSC) of PD patients harboring the A53T mutation within the SNCA gene, we confirm the reduction of insoluble SNCA after treatment with rHsCTSD. Moreover, we demonstrate a decrease of pathological SNCA conformers in the brain and within primary neurons of a ctsd-deficient mouse model after dosing with rHsCTSD. Boosting lysosomal CTSD activity not only enhanced SNCA clearance in human and murine neurons as well as tissue, but also restored endo-lysosome and autophagy function. Our findings indicate that CTSD is critical for SNCA clearance and function. Thus, enzyme replacement strategies utilizing CTSD may also be of therapeutic interest for the treatment of PD and other synucleinopathies aiming to decrease the SNCA burden.Abbreviations: aa: amino acid; SNCA/α-synuclein: synuclein alpha; APP: amyloid beta precursor protein; BBB: blood brain barrier; BF: basal forebrain; CBB: Coomassie Brilliant Blue; CLN: neuronal ceroid lipofuscinosis; CNL10: neuronal ceroid lipofuscinosis type 10; Corr.: corrected; CTSD: cathepsin D; CTSB: cathepsin B; DA: dopaminergic; DA-iPSn: induced pluripotent stem cell-derived dopaminergic neurons; dox: doxycycline; ERT: enzyme replacement therapy; Fx: fornix, GBA/β-glucocerebrosidase: glucosylceramidase beta; h: hour; HC: hippocampus; HT: hypothalamus; i.c.: intracranially; IF: immunofluorescence; iPSC: induced pluripotent stem cell; KO: knockout; LAMP1: lysosomal associated membrane protein 1; LSDs: lysosomal storage disorders; MAPT: microtubule associated protein tau; M6P: mannose-6-phosphate; M6PR: mannose-6-phosphate receptor; MB: midbrain; mCTSD: mature form of CTSD; neurofil.: neurofilament; PD: Parkinson disease; proCTSD: proform of CTSD; PRNP: prion protein; RFU: relative fluorescence units; rHsCTSD: recombinant human proCTSD; SAPC: Saposin C; SIM: structured illumination microscopy; T-insol: Triton-insoluble; T-sol: Triton-soluble; TEM: transmission electron microscopy, TH: tyrosine hydroxylase; Thal: thalamus.
Keywords: alpha-synuclein; cathepsin D; lysosomal degradation; lysosomal storage disorders; parkinson disease; synucleinopathies

Reduced KCNQ4-encoded voltage-dependent potassium channel activity underlies impaired β-adrenoceptor-mediated relaxation of renal arteries in hypertension - Chadha, Preet S.; Zunke, Friederike; Zhu, Hai-Lei; Davis, Alison J.; Jepps, Thomas A.; Olesen, Soren P.; Cole, William C.; Moffatt, James D.; Greenwood, Iain A. (Hypertension, 2012)
KCNQ4-encoded voltage-dependent potassium (Kv7.4) channels are important regulators of vascular tone that are severely compromised in models of hypertension. However, there is no information as to the role of these channels in responses to endogenous vasodilators. We used a molecular knockdown strategy, as well as pharmacological tools, to examine the hypothesis that Kv7.4 channels contribute to β-adrenoceptor-mediated vasodilation in the renal vasculature and underlie the vascular deficit in spontaneously hypertensive rats. Quantitative PCR and immunohistochemistry confirmed gene and protein expression of KCNQ1, KCNQ3, KCNQ4, KCNQ5, and Kv7.1, Kv7.4, and Kv7.5 in rat renal artery. Isoproterenol produced concentration-dependent relaxation of precontracted renal arteries and increased Kv7 channel currents in isolated smooth muscle cells. Application of the Kv7 blocker linopirdine attenuated isoproterenol-induced relaxation and current. Isoproterenol-induced relaxations were also reduced in arteries incubated with small interference RNAs targeted to KCNQ4 that produced a ≈60% decrease in Kv7.4 protein level. Relaxation to isoproterenol and the Kv7 activator S-1 were abolished in arteries from spontaneously hypertensive rats, which was associated with ≈60% decrease in Kv7.4 abundance. This study provides the first evidence that Kv7 channels contribute to β-adrenoceptor-mediated vasodilation in the renal vasculature and that abrogation of Kv7.4 channels is strongly implicated in the impaired β-adrenoceptor pathway in spontaneously hypertensive rats. These findings may provide a novel pathogenic link between arterial dysfunction and hypertension. © 2012 American Heart Association, Inc.
CRIS-Team Scopus Importer:2020-10-21
Keywords: β-adrenoceptor; KCNQ; Kv7 channels; renal artery; spontaneously hypertensive rat; vascular smooth muscle; vasodilation

Rescue of α-synuclein aggregation in Parkinson's patient neurons by synergistic enhancement of ER proteostasis and protein trafficking - Stojkovska, Iva; Wani, Willayat Y.; Zunke, Friederike; Belur, Nandkishore R.; Pavlenko, Egor A.; Mwenda, Nkatha; Sharma, Karan; Francelle, Laetitia; Mazzulli, Joseph R. (Neuron, 2022)
Neurodegenerative disorders are characterized by a collapse in proteostasis, as shown by the accumulation of insoluble protein aggregates in the brain. Proteostasis involves a balance of protein synthesis, folding, trafficking, and degradation, but how aggregates perturb these pathways is unknown. Using Parkinson's disease (PD) patient midbrain cultures, we find that aggregated α-synuclein induces endoplasmic reticulum (ER) fragmentation and compromises ER protein folding capacity, leading to misfolding and aggregation of immature lysosomal β-glucocerebrosidase. Despite this, PD neurons fail to initiate the unfolded protein response, indicating perturbations in sensing or transducing protein misfolding signals in the ER. Small molecule enhancement of ER proteostasis machinery promotes β-glucocerebrosidase solubility, while simultaneous enhancement of trafficking improves ER morphology, lysosomal function, and reduces α-synuclein. Our studies suggest that aggregated α-synuclein perturbs the ability of neurons to respond to misfolded proteins in the ER, and that synergistic enhancement of multiple proteostasis branches may provide therapeutic benefit in PD.
CRIS-Team Scopus Importer:2022-02-11
Keywords: alpha-synuclein; beta-glucocerebrosidase; ER stress; iPSC-derived midbrain dopaminergic neurons; lysosomal dysfunction; Parkinson's disease; protein aggregation

Reversible Conformational Conversion of α-Synuclein into Toxic Assemblies by Glucosylceramide - Zunke, Friederike; Moise, Alexandra C.; Belur, Nandkishore R.; Gelyana, Eilrayna; Stojkovska, Iva; Dzaferbegovic, Haris; Toker, Nicholas J.; Jeon, Sohee; Fredriksen, Kristina; Mazzulli, Joseph R. (Neuron, 2018)
α-Synuclein (α-syn) aggregation is a key event in Parkinson's disease (PD). Mutations in glycosphingolipid (GSL)-degrading glucocerebrosidase are risk factors for PD, indicating that disrupted GSL clearance plays a key role in α-syn aggregation. However, the mechanisms of GSL-induced aggregation are not completely understood. We document the presence of physiological α-syn conformers in human midbrain dopamine neurons and tested their contribution to the aggregation process. Pathological α-syn assembly mainly occurred through the conversion of high molecular weight (HMW) physiological α-syn conformers into compact, assembly-state intermediates by glucosylceramide (GluCer), without apparent disassembly into free monomers. This process was reversible in vitro through GluCer depletion. Reducing GSLs in PD patient neurons with and without GBA1 mutations diminished pathology and restored physiological α-syn conformers that associated with synapses. Our work indicates that GSLs control the toxic conversion of physiological α-syn conformers in a reversible manner that is amenable to therapeutic intervention by GSL reducing agents. Zunke et al. found that glycosphingolipids that accumulate in Gaucher disease cause a reversible structural change in Parkinson's protein α-synuclein, promoting its aggregation and toxicity. In patient-derived midbrain dopamine neurons, glycosphingolipid reduction restored physiological α-synuclein conformers and diminished pathology.
CRIS-Team Scopus Importer:2020-10-21
Keywords: Gaucher disease; GBA1; glucocerebrosidase; iPS-derived dopaminergic neurons; Lewy body; lysosomal storage disease; Parkinson's disease; protein aggregation; α-synuclein

SARS-CoV-2 Spike Protein Induces Time-Dependent CTSL Upregulation in HeLa Cells and Alveolarspheres - Bolsinger, Magdalena; Drobny, Alice; Wilfling, Sibylle; Reischl, Stephanie; Krach, Florian; Moritz, Raul; Balta, Denise; Hehr, Ute; Sock, Elisabeth; Bleibaum, Florian; Hanses, Frank; Winner, Beate; et al. (Journal of Cellular Biochemistry, 2024)
Autophagy and lysosomal pathways are involved in the cell entry of SARS-CoV-2 virus. To infect the host cell, the spike protein of SARS-CoV-2 binds to the cell surface receptor angiotensin-converting enzyme 2 (ACE2). To allow the fusion of the viral envelope with the host cell membrane, the spike protein has to be cleaved. One possible mechanism is the endocytosis of the SARS-CoV-2–ACE2 complex and subsequent cleavage of the spike protein, mainly by the lysosomal protease cathepsin L. However, detailed molecular and dynamic insights into the role of cathepsin L in viral cell entry remain elusive. To address this, HeLa cells and iPSC-derived alveolarspheres were treated with recombinant SARS-CoV-2 spike protein, and the changes in mRNA and protein levels of cathepsins L, B, and D were monitored. Additionally, we studied the effect of cathepsin L deficiency on spike protein internalization and investigated the influence of the spike protein on cathepsin L promoters in vitro. Furthermore, we analyzed variants in the genes coding for cathepsin L, B, D, and ACE2 possibly associated with disease progression using data from Regeneron's COVID Results Browser and our own cohort of 173 patients with COVID-19, exhibiting a variant of ACE2 showing significant association with COVID-19 disease progression. Our in vitro studies revealed a significant increase in cathepsin L mRNA and protein levels following exposure to the SARS-CoV-2 spike protein in HeLa cells, accompanied by elevated mRNA levels of cathepsin B and D in alveolarspheres. Moreover, an increase in cathepsin L promoter activity was detected in vitro upon spike protein treatment. Notably, the knockout of cathepsin L resulted in reduced internalization of the spike protein. The study highlights the importance of cathepsin L and lysosomal proteases in the SARS-CoV-2 spike protein internalization and suggests the potential of lysosomal proteases as possible therapeutic targets against COVID-19 and other viral infections.
CRIS-Team Scopus Importer:2024-07-19
Keywords: cathepsin L; cathepsins; lysosomes; SARS-CoV-2; spike protein

Stress-Induced Cellular Clearance Is Mediated by the SNARE Protein ykt6 and Disrupted by α-Synuclein - Cuddy, Leah K.; Wani, Willayat Y.; Morella, Martino L.; Pitcairn, Caleb; Tsutsumi, Kotaro; Fredriksen, Kristina; Justman, Craig J.; Grammatopoulos, Tom N.; Belur, Nandkishore R.; Zunke, Friederike; Subramanian, Aarthi; Affaneh, Amira; et al. (Neuron, 2019)
Age-related neurodegenerative disorders are characterized by a slow, persistent accumulation of aggregated proteins. Although cells can elicit physiological responses to enhance cellular clearance and counteract accumulation, it is unclear how pathogenic proteins evade this process in disease. We find that Parkinson's disease α-synuclein perturbs the physiological response to lysosomal stress by impeding the SNARE protein ykt6. Cytosolic ykt6 is normally autoinhibited by a unique farnesyl-mediated regulatory mechanism; however, during lysosomal stress, it activates and redistributes into membranes to preferentially promote hydrolase trafficking and enhance cellular clearance. α-Synuclein aberrantly binds and deactivates ykt6 in patient-derived neurons, thereby disabling the lysosomal stress response and facilitating protein accumulation. Activating ykt6 by small-molecule farnesyltransferase inhibitors restores lysosomal activity and reduces α-synuclein in patient-derived neurons and mice. Our findings indicate that α-synuclein creates a permissive environment for aggregate persistence by inhibiting regulated cellular clearance and provide a therapeutic strategy to restore protein homeostasis by harnessing SNARE activity.
CRIS-Team Scopus Importer:2020-10-21
Keywords: induced pluripotent stem cells; lysosomal storage disease; lysosomal stress; Parkinson's disease; protein aggregation; proteomic stress; synucleinopathy

Structural and Functional Analyses of the Shedding Protease ADAM17 in HoxB8-Immortalized Macrophages and Dendritic-like Cells - Cabron, Anne-Sophie; El Azzouzi, Karim; Boss, Melanie; Arnold, Philipp; Schwarz, Jeanette; Rosas, Marcela; Dobert, Jan Philipp; Pavlenko, Egor; Schumacher, Neele; Renne, Thomas; Taylor, Philip R.; Linder, Stefan; et al. (Journal of Immunology, 2018)
A disintegrin and metalloproteinase (ADAM) 17 has been implicated in many shedding processes. Major substrates of ADAM17 are TNF-a, IL-6R, and ligands of the epidermal growth factor receptor. The essential role of the protease is emphasized by the fact that ADAM17 deficiency is lethal in mice. To study ADAM17 function in vivo, we generated viable hypomorphic ADAM17 mice called ADAM17ex/ex mice. Recent studies indicated regulation of proteolytic ADAM17 activity by cellular processes such as cytoplasmic phosphorylation and removal of the prodomain by furin cleavage. Maturation and thus activation of ADAM17 is not fully understood. So far, studies of ADAM17 maturation have been mainly limited to mouse embryonic fibroblasts or transfected cell lines relying on nonphysiologic stimuli such as phorbol esters, thus making interpretation of the results difficult in a physiologic context. In this article, we present a robust cell system to study ADAM17 maturation and function in primary cells of the immune system. To this end, HoxB8 conditionally immortalized macrophage precursor cell lines were derived from bone marrow of wild-type and hypomorphic ADAM17ex/ex mice, which are devoid of measurable ADAM17 activity. ADAM17 mutants were stably expressed in macrophage precursor cells, differentiated to macrophages under different growth factor conditions (M-CSF versus GM-CSF), and analyzed for cellular localization, proteolytic activity, and podosome disassembly. Our study reveals maturation and activity of ADAM17 in a more physiological-immune cell system. We show that this cell system can be further exploited for genetic modifications of ADAM17 and for studying its function in immune cells. The Journal of Immunology, 2018, 201: 3106-3118.
CRIS-Team Scopus Importer:2020-10-21

Structure of LIMP-2 provides functional insights with implications for SR-BI and CD36 - Neculai, Dante; Schwake, Michael; Ravichandran, Mani; Zunke, Friederike; Collins, Richard F.; Peters, Judith; Neculai, Mirela; Plumb, Jonathan; Loppnau, Peter; Pizarro, Juan Carlos; Seitova, Alma; Trimble, William S.; et al. (Nature, 2013)
Members of the CD36 superfamily of scavenger receptor proteins are important regulators of lipid metabolism and innate immunity. They recognize normal and modified lipoproteins, as well as pathogen-associated molecular patterns. The family consists of three members: SR-BI (which delivers cholesterol to the liver and steroidogenic organs and is a co-receptor for hepatitis C virus), LIMP-2/LGP85 (which mediates lysosomal delivery of β-glucocerebrosidase and serves as a receptor for enterovirus 71 and coxsackieviruses) and CD36 (a fatty-acid transporter and receptor for phagocytosis of effete cells and Plasmodium-infected erythrocytes). Notably, CD36 is also a receptor for modified lipoproteins and β-amyloid, and has been implicated in the pathogenesis of atherosclerosis and of Alzheimer's disease. Despite their prominent roles in health and disease, understanding the function and abnormalities of the CD36 family members has been hampered by the paucity of information about their structure. Here we determine the crystal structure of LIMP-2 and infer, by homology modelling, the structure of SR-BI and CD36. LIMP-2 shows a helical bundle where β-glucocerebrosidase binds, and where ligands are most likely to bind to SR-BI and CD36. Remarkably, the crystal structure also shows the existence of a large cavity that traverses the entire length of the molecule. Mutagenesis of SR-BI indicates that the cavity serves as a tunnel through which cholesterol(esters) are delivered from the bound lipoprotein to the outer leaflet of the plasma membrane. We provide evidence supporting a model whereby lipidic constituents of the ligands attached to the receptor surface are handed off to the membrane through the tunnel, accounting for the selective lipid transfer characteristic of SR-BI and CD36. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2020-10-21

The function of lysosomes and their role in Parkinson's disease - Zunke, Friederike (Neuroforum, 2020)
Lysosomes are cellular organelles that are important for the degradation and recycling of various biomolecules. Specialized lysosomal membrane proteins, as well as soluble enzymes, are important for the efficient turn-over of lysosomal substrates. A deficiency in the degradative capacity of lysosomes leads to severe pathologies referred to as lysosomal storage disorders. There is increasing evidence for the importance of lysosomal function in neurodegenerative disorders, including Parkinson's disease. One reason for this might be the vulnerability of neuronal cells. Since neurons do not undergo further cell division, non-degraded substrates accumulate in aging cells, causing a buildup of toxicity. Recent genomic screenings identified a number of lysosome-associated genes as potential risk factors for Parkinson's disease, which are discussed in this review. Moreover, it is outlined how targeting lysosomal function might help in developing novel therapeutic strategies.
CRIS-Team Scopus Importer:2020-10-21
Keywords: lysosomal enzymes; lysosomal storage disorders (LSD); lysosomes; Parkinson's disease; α-synuclein

The Quest for Anti-α-Synuclein Antibody Specificity—Lessons Learnt From Flow Cytometry Analysis - Leupold, Lukas; Sigutova, Veronika; Gerasimova, Elizaveta; Regensburger, Martin; Zundler, Sebastian; Zunke, Friederike; Xiang, Wei; Winner, Beate; Prots, Iryna (Frontiers in Neurology, 2022)
The accumulation of alpha-synuclein (aSyn) is the hallmark of a group of neurodegenerative conditions termed synucleopathies. Physiological functions of aSyn, including those outside of the CNS, remain elusive. However, a reliable and reproducible evaluation of aSyn protein expression in different cell types and especially in low-expressing cells is impeded by the existence of a huge variety of poorly characterized anti-aSyn antibodies and a lack of a routinely used sensitive detection methods. Here, we developed a robust flow cytometry-based workflow for aSyn detection and antibody validation. We test our workflow using three commercially available antibodies (MJFR1, LB509, and 2A7) in a variety of human cell types, including induced pluripotent stem cells, T lymphocytes, and fibroblasts, and provide a cell- and antibody-specific map for aSyn expression. Strikingly, we demonstrate a previously unobserved unspecificity of the LB509 antibody, while the MJFR1 clone revealed specific aSyn binding however with low sensitivity. On the other hand, we identified an aSyn-specific antibody clone 2A7 with an optimal sensitivity for detecting aSyn in a range of cell types, including those with low aSyn expression. We further utilize our workflow to demonstrate the ability of the 2A7 antibody to distinguish between physiological differences in aSyn expression in neuronal and non-neuronal cells from the cortical organoids, and in neural progenitors and midbrain dopaminergic neurons from healthy controls and in patients with Parkinson's disease who have aSyn gene locus duplication. Our results provide a proof of principle for the use of high-throughput flow cytometry-based analysis of aSyn and highlight the necessity of rigorous aSyn antibody validation to facilitate the research of aSyn physiology and patholog
Keywords: alpha-synuclein; antibodies; synuclein antibodies; T cell; antibody specificity; flow cytometry; α-synuclein expression

Therapeutic potential of lysosomal cathepsins for neurodegenerative diseases - Prieto Huarcaya, Susy; Zunke, Friederike (Neural Regeneration Research, 2023)
EVALuna2:540278

The role of lysosomal cathepsins in neurodegeneration: Mechanistic insights, diagnostic potential and therapeutic approaches - Drobny, Alice; Prieto Huarcaya, Susy; Dobert, Jan; Kluge, Annika; Bunk, Josina; Schlothauer, Theresia; Zunke, Friederike (Biochimica Et Biophysica Acta-Molecular Cell Research, 2022)
Lysosomes are ubiquitous organelles with a fundamental role in maintaining cellular homeostasis by mediating degradation and recycling processes. Cathepsins are the most abundant lysosomal hydrolyses and are responsible for the bulk degradation of various substrates. A correct autophagic function is essential for neuronal survival, as most neurons are post-mitotic and thus susceptible to accumulate cellular components. Increasing evidence suggests a crucial role of the lysosome in neurodegeneration as a key regulator of aggregation-prone and disease-associated proteins, such as α-synuclein, β-amyloid and huntingtin. Particularly, alterations in lysosomal cathepsins CTSD, CTSB and CTSL can contribute to the pathogenesis of neurodegenerative diseases as seen for neuronal ceroid lipofuscinosis, synucleinopathies (Parkinson's disease, Dementia with Lewy Body and Multiple System Atrophy) as well as Alzheimer's and Huntington's disease. In this review, we provide an overview of recent evidence implicating CTSD, CTSB and CTSL in neurodegeneration, with a special focus on the role of these enzymes in α-synuclein metabolism. In addition, we summarize the potential role of lysosomal cathepsins as clinical biomarkers in neurodegenerative diseases and discuss potential therapeutic approaches by targeting lysosomal function.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Alzheimer's disease; Cathepsins; Huntington's disease; Lysosome; Neurodegeneration; Neuronal ceroid lipofuscinosis; Parkinson's disease; Synucleinopathies; α-Synuclein

The role of lysosomes in alpha-synucleinopathies: A focus on glial cells - Balta, Denise; Zunke, Friederike (Neural Regeneration Research, 2022)
CRIS-Team Scopus Importer:2022-01-07

The role of triggering receptor expressed on myeloid cells 2 in Parkinson's disease and other neurodegenerative disorders - Schwarz, Hannah; Bässler, Sarah; Balta, Denise; Socher, Eileen; Zunke, Friederike; Arnold, Philipp (Behavioural Brain Research, 2022)
Parkinson's disease (PD) is a progressive neurological disorder marked by cardinal clinical symptoms such as rigor, tremor, and akinesia. Albeit a loss of dopaminergic neurons from the substantia nigra pars compacta is causative for the movement impairments found in patients, molecular reasoning for this loss is still incomplete. In recent years, triggering factor expressed on myeloid cells (TREM2) gained attention in the field of neurodegeneration as it could be associated with different neurodegenerative disorders. Primarily identified as a risk factor in Alzheimer's disease, variants in TREM2 were linked to PD and multiple sclerosis, too. Expressed on phagocytic cells, such as macrophages and microglia, TREM2 puts the focus on inflammation associated conditions in PD and provides a molecular target that could at least partly explain the role of immune cells in PD. Here, we summarize expression patterns and molecular functions of TREM2, recapitulate on its role in inflammation, phagocytosis and cell survival, before turning to neurodegenerative disorders with an emphasis on PD.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Cell signaling; DAP12; Inflammation; Neurodegeneration; Parkinson's disease; TREM2

The shedding protease ADAM17: Physiology and pathophysiology - Zunke, Friederike; Rose-John, Stefan (Biochimica Et Biophysica Acta-Molecular Cell Research, 2017)
The disintegrin metalloprotease ADAM17 has been a matter of intense studies aiming to unravel structure, function and regulation of protease expression, maturation and activity. In this review, we summarize data on the physiological role of ADAM17 in health and disease. Here we provide an overview of ADAM17 substrates, mouse models of ADAM17-deficiencies and discuss recent findings of ADAM17 function in the immune system and central nervous system as well as in cancer. Whereas ADAM17 function in EGF-R-, in Interleukin-6 (IL-6)- and in TNFα-biology has been shown to play a decisive role in regulation of the immune system as well as cancer development, the role of ADAM17 in the central nervous system and neurodegeneration still remains elusive. We show ADAM17 expression in human dopaminergic neurons derived from induced pluripotent stem cells and we discuss how this state-of-the-art technology can be further exploited to study the function of this important protease in the brain and other tissues. This article is part of a Special Issue entitled: Proteolysis as a Regulatory Event in Pathophysiology edited by Stefan Rose-John.
CRIS-Team Scopus Importer:2020-10-21
Keywords: ADAM proteases; ADAM17; EGF receptor; IL-6 trans-signaling; IL-6R; iPS cell system; Shedding

Toxic Metamorphosis-How Changes from Lysosomal to Cytosolic pH Modify the Alpha-Synuclein Aggregation Pattern - Eymsh, Bisher; Drobny, Alice; Heyn, Timon R.; Xiang, Wei; Lucius, Ralph; Schwarz, Karin; Keppler, Julia K.; Zunke, Friederike; Arnold, Philipp (Biomacromolecules, 2020)
Alpha-synuclein (aSyn) is a cytosolic, aggregation-prone protein that is associated with neurodegenerative disorders like Parkinsons disease. Interestingly, the protein can appear in different conformations, including monomeric and oligomeric forms as well as amyloid fibrils. Its individual structural constituents seem to be dependent on various factors and the composition of the respective cellular surroundings. Although under physiological conditions, most aSyn is found in the cytosol and synapses of neurons, aSyn can also be found in lysosomal compartments, where it gets degraded. We here compare the assembly speed, morphology, folding state, and spreading of aSyn at cytosolic pH (pH 7.4) and lysosomal pH (pH 5) using Thioflavin T, transmission electron microscopy, circular dichroism, and Fourier transform infrared spectroscopy. Interestingly, we found substantial differences between aSyn aggregation under neutral and acidic pH conditions, like those present in cytosolic and lysosomal cellular compartments. Also, lysosomal aSyn enriched from an aSyn-overexpressing cell line was able to seed aggregation in a concentration-dependent manner. Moreover, we observed that aSyn aggregates formed under in vitro lysosomal pH (pH 5) conditions were not stable at neutral pH and collapsed into partly soluble aggregates with changed structural characteristics. Our findings have meaningful implications in intracellular toxicity events as well as in lysis procedures for molecular and structural characterization of intracellular aSyn conformers.
CRIS-Team WoS Importer:2021-01-15

α-Synuclein-induced lysosomal dysfunction occurs through disruptions in protein trafficking in human midbrain synucleinopathy models - Mazzulli, Joseph R.; Zunke, Friederike; Isacson, Ole; Studer, Lorenz; Krainc, Dimitri (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Parkinson's disease (PD) is an age-related neurodegenerative disorder characterized by the accumulation of protein aggregates comprised of α-synuclein (α-syn). A major barrier in treatment discovery for PD is the lack of identifiable therapeutic pathways capable of reducing aggregates in human neuronal model systems. Mutations in key components of protein trafficking and cellular degradation machinery represent important risk factors for PD; however, their precise role in disease progression and interaction with α-syn remains unclear. Here, we find that α-syn accumulation reduced lysosomal degradation capacity in human midbrain dopamine models of synucleinopathies through disrupting hydrolase trafficking. Accumulation of α-syn at the cell body resulted in aberrant association with cis-Golgi-tethering factor GM130 and disrupted the endoplasmic reticulum-Golgi localization of rab1a, a key mediator of vesicular transport. Overexpression of rab1a restored Golgi structure, improved hydrolase trafficking and activity, and reduced pathological α-syn in patient neurons. Our work suggests that enhancement of lysosomal hydrolase trafficking may prove beneficial in synucleinopathies and indicates that human midbrain disease models may be useful for identifying critical therapeutic pathways in PD and related disorders.
CRIS-Team Scopus Importer:2020-10-21
Keywords: Induced pluripotent stem cells; Long-term midbrain culture; Parkinson's disease; Protein trafficking; Synucleinopathies

α-Synuclein in Parkinson’s disease: causal or bystander? - Riederer, Peter; Berg, Daniela; Casadei, Nicolas; Cheng, Fubo; Classen, Joseph; Dresel, Christian; Jost, Wolfgang; Krüger, Rejko; Müller, Thomas; Reichmann, Heinz; Rieß, Olaf; Storch, Alexander; et al. (Journal of Neural Transmission, 2019)
Parkinson’s disease (PD) comprises a spectrum of disorders with differing subtypes, the vast majority of which share Lewy bodies (LB) as a characteristic pathological hallmark. The process(es) underlying LB generation and its causal trigger molecules are not yet fully understood. α-Synuclein (α-syn) is a major component of LB and SNCA gene missense mutations or duplications/triplications are causal for rare hereditary forms of PD. As typical sporadic PD is associated with LB pathology, a factor of major importance is the study of the α-syn protein and its pathology. α-Syn pathology is, however, also evident in multiple system atrophy (MSA) and Lewy body disease (LBD), making it non-specific for PD. In addition, there is an overlap of these α-synucleinopathies with other protein-misfolding diseases. It has been proven that α-syn, phosphorylated tau protein (pτ), amyloid beta (Aβ) and other proteins show synergistic effects in the underlying pathogenic mechanisms. Multiple cell death mechanisms can induce pathological protein-cascades, but this can also be a reverse process. This holds true for the early phases of the disease process and especially for the progression of PD. In conclusion, while rare SNCA gene mutations are causal for a minority of familial PD patients, in sporadic PD (where common SNCA polymorphisms are the most consistent genetic risk factor across populations worldwide, accounting for 95% of PD patients) α-syn pathology is an important feature. Conversely, with regard to the etiopathogenesis of α-synucleinopathies PD, MSA and LBD, α-syn is rather a bystander contributing to multiple neurodegenerative processes, which overlap in their composition and individual strength. Therapeutic developments aiming to impact on α-syn pathology should take this fact into consideration.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Autophagy; Gene expression; Lysosome; Neuroinflammation; Neuromelanin; Parkinson’s disease; Proteasome; Protein interactions; SNCA gene; Synucleinopathy; Therapy; α-Synuclein

α-Synuclein Seed Amplification Assays from Blood-Based Extracellular Vesicles in Parkinson's Disease: An Evaluation of the Evidence - Bernhardt, Alexander Maximilian; Nemati, Mojtaba; Boros, Fanni Annamaria; Hopfner, Franziska; Levin, Johannes; Mollenhauer, Brit; Winkler, Jürgen; Zerr, Inga; Zunke, Friederike; Höglinger, Günter (Movement Disorders, 2024)
CRIS-Team Scopus Importer:2024-07-19